Long‐term clinical outcomes of endoscopic submucosal dissection for colorectal neoplasia with or without the hybrid technique. (29th September 2020) - Kang, DU; Park, JC; Hwang, SW; Park, SH; Yang, DH; Kim, KJ; Ye, BD; Myung, SJ; Yang, SK; Byeon, JS
Abstract: Aim: The main aim of this study was to compare the long‐term outcome of a conventional colorectal endoscopic submucosal dissection (ESD) in which submucosal dissection was continued throughout until the completion of resection (ESD‐T) to hybrid endoscopic submucosal dissection (ESD‐H) in the colorectum. Method: Medical records of 836 colorectal neoplasia patients treated by ESD‐T or ESD‐H were reviewed. ESD‐H was defined as colorectal ESD with additional snaring in the final stage of the procedure. Primary outcomes were the overall and metastatic recurrence rates. Secondary outcomes were short‐term outcomes such as the en bloc resection rate, procedure time and adverse events. Results: The overall recurrence rate was higher in the ESD‐H than in the ESD‐T group (5.7% vs 0.7%, P  = 0.001). The metastatic recurrence rate showed no significant difference between these groups (1.4% vs 1.4%, P  = 1.000). Multivariate analysis revealed that a failed en bloc resection (hazard ratio 24.097; 95% CI 5.446–106.237; P  < 0.001) and larger tumour size (hazard ratio 1.042; 95% CI 1.014–1.070; P  = 0.003) were independently associated with overall recurrence. The ESD‐H group showed a lower en bloc resection rate (56.8% vs 96.5%, P  < 0.001), shorter procedure time (45.6 vs 54.3 min, P  < 0.001) and higher perforation rate (10.3% vs 6.0%, P  = 0.029). Conclusion: Although long‐term outcomes in terms of overall recurrence are inferior following ESD‐H, a failed en bloc resection and large tumour size are the only independent risk factors for recurrence. Further investigations are warranted to improve the long‐term outcomes of ESD‐H.